Long‐term outcomes of direct acting antivirals in post‐transplant advanced hepatitis C virus recurrence and fibrosing cholestatic hepatitis. Issue 10 (5th May 2017) - Vukotic, R.; Conti, F.; Fagiuoli, S.; Morelli, M. C.; Pasulo, L.; Colpani, M.; Foschi, F. G.; Berardi, S.; Pianta, P.; Mangano, M.; Donato, M. F.; Malinverno, F.; et al.
Summary: Long‐term functional outcomes of sofosbuvir‐based antiviral treatment were evaluated in a cohort study involving 16 Italian centres within the international compassionate use programme for post‐transplant hepatitis C virus (HCV) recurrence. Seventy‐three patients with cirrhosis (n=52) or fibrosing cholestatic hepatitis (FCH, n=21) received 24‐week sofosbuvir with ribavirin±pegylated interferon or interferon‐free sofosbuvir‐based regimen with daclatasvir/simeprevir+ribavirin. The patients were observed for a median time of 103 (82‐112) weeks. Twelve of 73 (16.4%) died (10 non‐FCH, 2 FCH) and two underwent re‐LT. Sustained virological response was achieved in 46 of 66 (69.7%): 31 of 47 (66%) non‐FCH and 15 of 19 (79%) FCH patients. All relapsers were successfully retreated. Comparing the data of baseline with last follow‐up, MELD and Child‐Turcotte‐Pugh scores improved both in non‐FCH (15.3±6.5 vs 10.5±3.8, P <.0001 and 8.4±2.1 vs 5.7±1.3, P <.0001, respectively) and FCH (17.3±5.9 vs 10.1±2.8, P =.001 and 8.2±1.6 vs 5.5±1, P =.001, respectively). Short‐treatment mortality was higher in patients with baseline MELD≥25 than in those with MELD<25 (42.9% vs 4.8%, P =.011). Long‐term mortality was 53.3% among patients with baseline MELD≥20 and 7.5% among those with MELD<20 ( P <.0001). Among deceased patients 75% were Child‐Turcotte‐Pugh class C at baseline, while among survivors 83.9% were class A or B ( P <.0001). Direct acting antivirals‐based treatments for severe post‐transplant hepatitis C recurrence, comprising fibrosing cholestatic hepatitis, significantly improve liver function, even without viral clearance and permit an excellent long‐term survival. The setting of severe HCV recurrence may require the identification of "too‐sick‐to‐treat patients" to avoid futile treatments.